The effectiveness of using the envemath learning application to improve students' critical thinking skills - Novitaningsih, Yossi; Nafida Hetty Marhaeni (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Critical thinking skills are essential skills in the 21st century. With the development of ICT, critical thinking skills can be integrated with learning applications. The purpose of this study is to determine the effectiveness of using the EnveMath learning application to improve students' critical thinking skills. This type of research is an experimental research with a pretest posttest control group design. The population used in this study is grade VIII students at SMP Negeri 11 Yogyakarta. The sample in this study is class VIII C as an experimental class and class VIII D as a control class with each class totaling 34 students. The data collection technique uses interviews, observations, and critical thinking test questions on opportunity materials. The results of the study show that the use of the EnveMath learning application is effective in improving critical thinking skills. This is because the EnveMath learning application guides students in analyzing mathematical problems logically and systematically through critical thinking indicators presented in the application. This is supported by the results of the statistical data test which is based on the Wilcoxon Signed Ranks Test test from the experimental class and the control class has a sig. (2-tailed) < 0.05, the Mann-Whitney U Test has a sig. (2-tailed) < 0.05 which means that the use of the EnveMath learning application in the classroom is more effective than the class that does not use the EnveMath learning application. Then, the mean difference test shows that the average increase in the experimental class is greater than the average increase in the control class (49.26 > 25.41). Thus, the use of the EnveMath learning application during learning Mathematics is effective in improving students' critical thinking skills.